ANALISIS DAYA SAING PERIKANAN CAKALANG (KATSUWONUS PELAMIS) PADA ALAT TANGKAP PURSE SEINE - Mrs Fajriah (Universitas Negeri Medan, 2014)
Skipjack fishery business is one of businesses in catch fisheries sector whichis potential to be developed since it has the ability to increase fishermen’sincome and macro economy. This research was aimed to analyze: a) Competitiveness of skipjack fisheries bussines the Purse Seine Fishermen Capture Device Kendari at WPP 714 on comparative and competitive advantages, b) the impact of policy on the competitiveness of skipjack fishery business in Kendari. The research was carried out for seven months from December 2013 to July 2014 in Kendari, the center of catch fisheries in Southeast Sulawesi. The sampling is done by simple random sampling. The data was analyzed by using Policy Matrix Analysis (PAM) model. The result showed that; Skipjack fishery business using in Kendari has a good competitiveness in both domestic and international market. This result implied that the skipjack fishery business in Kendari is economically and financially feasible, and will become more competitive if supported by government’s policy on input and output prices of the skipjack fishery business.